Effects of Aloe vera Gel Coating on Quality and Shelf Life of Lime (Citrus aurantifolia) Fruit During Ambient Storage - Orawan Pimsorn; Somsak Kramchote; Patcharaporn Suwor (My University, 2022)
Lime (Citrus aurantiifolia var. Pan) fruits were coated with Aloe vera gel (AVG) at 0 (distilled water as control), 10, 20, 30, 40, and 50% concentration as a 5 min dip and stored at ambient temperature (29 ± 1°C, 74 ± 5% RH) for 16 days. AVG coating markedly slowed fruit yellowing based on color scores and CIE L*, a*, and b* values, resulting in an increase in shelf life of about four days longer than that of the control (10 days). It did not significantly affect other fruit responses; AVG-coated and uncoated fruit had comparable weight loss, juice content, total soluble solids (TSS), titratable acidity (TA), and vitamin C content. Thus, AVG coating improved shelf life of lime primarily through delayed yellowing without adverse effects on other physicochemical attributes.
Keywords: Aloe Vera; Titratable acid; Distilled water; Postharvest Quality and Shelf Life Management